2011
DOI: 10.1016/j.immuni.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Contrastingly Affects Bacterial Infection and Experimental Colitis by Inhibiting Nuclear Factor-κB-Inducible Immune Pathways

Abstract: SummaryErythropoietin (EPO) is the principal cytokine regulating erythropoiesis through its receptor, EPOR. Interestingly, EPORs are also found on immune cells with incompletely understood functions. Here, we show that EPO inhibits the induction of proinflammatory genes including tumor necrosis factor (TNF)-α and inducible nitric oxide (NO) synthase in activated macrophages, which is mechanistically attributable to blockage of nuclear factor (NF)-κB p65 activation by EPO. Accordingly, in systemic Salmonella in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
195
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(213 citation statements)
references
References 47 publications
15
195
3
Order By: Relevance
“…A negative correlation was found between the levels of hepcidin mRNA and serum EPO. A recent study has demonstrated that EPO inhibits the induction of IL-6 in macrophages after LPS treatment or in spleens of mice after Salmonella infection (37). The action mediated by EPO is attributable to blockage of NF-kB p65 activation.…”
Section: Discussionmentioning
confidence: 98%
“…A negative correlation was found between the levels of hepcidin mRNA and serum EPO. A recent study has demonstrated that EPO inhibits the induction of IL-6 in macrophages after LPS treatment or in spleens of mice after Salmonella infection (37). The action mediated by EPO is attributable to blockage of NF-kB p65 activation.…”
Section: Discussionmentioning
confidence: 98%
“…5 Analogously, finding that EPO inhibits T-cell expansion in response to polyclonal stimuli and prevents Th1 differentiation of naïve CD4 + T cells may partially explain previous data showing that EPO downregulates proinflammatory immune effector pathways in response to chemical tissue damage, LPS stimulation, and Salmonella infection. 6,[30][31][32] In patients with rheumatoid arthritis, treatment with recombinant EPO not only resulted in amelioration of anemia but also improved disease activity. 33 Intriguingly, EPO has been associated with adverse outcomes of tumor progression and impaired survival in a series of clinical trials, 34,35 a finding that might be explained, at least in part, by EPO-induced inhibition of antitumor T-cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A primary characteristic of this program is expression of a specific tissue-protective receptor (TPR) (stage 3) and, after a significant time delay (hours) (7), expression of its ligand, which is now known to be erythropoietin (EPO) (stage 4). EPO signals through the TPR to inhibit proinflammatory cytokine production (8), inhibit macrophage activity (9) and delimit the volume of injury by counteracting apoptosis (10) (stage 5). The TPR also acts to recruit vascularand tissue-specific stem cells (11) and enhances tissue repair (12) (stage 6).…”
Section: The Receptor That Tames the Innate Immune Responsementioning
confidence: 99%
“…A variety of tissues that have been examined for expression of βCR and EPOR, including the central ( Figure 4A [35]) and peripheral (43) nervous systems, retina (44), heart (45), kidney (46), muscle (47) and the endothelium (48). Additionally, components of the immune system that are resident or migrate to regions of injury also highly express subunits for the TPR as, for example, specific subsets of macrophages (9).…”
Section: Epo Receptor Isoformsmentioning
confidence: 99%
See 1 more Smart Citation